Expert Consensus on the Use of a New Bioengineered, Cell-Friendly, Smooth Surface Breast Implant. (8th April 2019) - Sforza, Marcos; Hammond, Dennis C; Botti, Giovanni; Hedén, Per; Chacón Quirós, Manuel; Munhoz, Alexandre Mendonça; Kinney, Brian M; Corduff, Niamh
Abstract: Background: Although general guidelines are available for established silicone gel breast implants, the unique characteristics of the latest Motiva implants warrant specific guidelines. Objectives: This study aimed to generate consensus recommendations and summarize expert-based advice to better understand current surgical practices and to establish guidelines for surgeons transitioning from other implant devices to the Motiva implants. Methods: A survey was compiled by 12 plastic surgeon experts in aesthetic and reconstructive breast surgery and 1 biotechnology scientist, and distributed to 36 plastic surgeons to establish a consensus on the use of these devices. Surgical techniques, complication rates, and implant selection were among the topics discussed. Results: The experts agreed on 3 core principles regarding the use of Motiva Round and Ergonomix implants. Firstly, the dissected pocket needs to be close fitting and steps must be taken to prevent expansion of the pocket. Secondly, implant selection must be individualized. Finally, surgical planning and technique must be carefully considered. When questioned about problems they had ecountered, 84.6% of the experts agreed that they experienced fewer overall complications and 76.9% confirmed reduced capsular contracture rates with these devices. Overall, 84.6% of the experts favored selecting Motiva Ergonomix implants over Round implants to achieve a more natural look. In addition, 92.3% of the experts agreed that Motiva implants, due to their innovative technology, reduce the risk of anaplastic large-cell lymphoma. Conclusions: This international consensus of leading practitioners will assist plastic surgeons with patient selection, preoperative planning, and surgical technique. These recommendations are designed to optimize surgical outcomes, resulting in lower overall complication rates, more natural-looking breasts, and highly satisfied patients.